Breaking the Glass Ceiling: A Multiregional Study of Mentorship and Leadership in All-Women Surgical Teams - Bustamante A; Salazar Lopez BB; Jones EM; Turk M; Tapia Arellano MF; Treminio S; Rata MJ; Msokera C; Daradkeh H; Barkhordarzadeh AD; Umutoni A; Bautista A; et al. (Dove Medical Press, 2024)
Atenas Bustamante,1 Barbara Beatriz Salazar Lopez,1,* Emily Marie Jones,1,* Marvee Turk,2 Maria Fernanda Tapia Arellano,1 Sonia Treminio,1 Mikyla Jade Rata,1 Chifundo Msokera,1,3,4 Hebah Daradkeh,1 Ainaz Dory Barkhordarzadeh,5 Alice Umutoni,1 Alyssa Bautista,1 Priyanka Naidu,2 Naikhoba C O Munabi,2 William P Magee III,1,2 Elizabeth A Cote,1 Kathy Magee,1 Allyn Auslander1 1Operation Smile Inc., Virginia Beach, VA, USA; 2Division of Plastic and Maxillofacial Surgery, Children's Hospital Los Angeles, Los Angeles, CA, USA; 3Department of Clinical Medicine, University of Oxford, Oxford, England; 4Clinical Services, Ministry of Health, Lilongwe, Malawi; 5David Geffen School of Medicine, University of California Los Angeles, Los Angeles, CA, USA*These authors contributed equally to this workCorrespondence: Allyn Auslander, Research and Innovation, Operation Smile Inc., Virginia Beach, VA, USA, Email allyn.auslander@operationsmile.orgBackground: Globally, billions of people lack access to safe surgical care. Women represent a valuable resource to tackle the healthcare workforce shortage which impedes the delivery of surgery. With women entering the global health workforce at an increasing rate, Operation Smile (OS) launched the Women in Medicine program to create women-led leadership and mentorship opportunities for women healthcare workers to empower them to become leaders in healthcare.Purpose: This multi-regional study aims to evaluate the experiences of healthcare providers on OS all-women surgical programs and the impact of participation on leadership and mentorship opportunities.Methods: In 2022, OS conducted four cleft surgical programs with all-women providers in Morocco, Peru, Malawi, and the Philippines. Providers from various specialties participating in the programs were surveyed. Participants were invited to complete the surveys anonymously in the final two days of each program. Analysis involved descriptive statistics and chi-square tests.Results: Across all programs, 215 providers from 36 countries were surveyed. Ninety-seven percent of participants reported improvement in their technical and non-technical skills. Eighty-two percent reported that the program motivated them to seek leadership positions, despite only 37% having prior leadership experience on an OS program. Participating in an all-women team motivated 96% to seek mentorship from another woman and 99% to mentor others. Overall, 98% of providers across all regions and specialties supported the importance of women leadership, and 95% endorsed women mentorship.Conclusion: Promoting gender equity is crucial to address the ongoing healthcare workforce shortage and improve access to safe surgical care. This study demonstrates the importance of mentorship between women to advance into leadership positions. Programs that provide women in healthcare with educational, mentorship, and leadership opportunities can effectively equip them with the skills needed to advance their careers and strengthen the global workforce.Keywords: gender equity, healthcare workforce, surgery, global health